THE RELIGIOUS-CULTURAL ASPECT OF KANJENG GUSTI PANGERAN ADIPATI ARYA (KGPAA) MANGKUNEGARA IX FUNERAL CEREMONY - Noviani, Nur Laili; Mustolehudin, Mustolehudin; Mardhiyani, Nur Laili; Muzayanah, Umi; Maknun, Moch. Lukluil (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
KGPAA Mangkunegara IX funeral ceremony has attracted much attention because he was the former ruler of Kadipaten Mangkunegaran Surakarta, Central Java and he died in the middle of activity restriction due to the pandemic Covid-19 in Indonesia. Pura Mangkunegaran has its funeral ceremony but it hasn’t been written in many textbooks. The religious and cultural aspect was included in that ceremony because Mangkunegara IX was a Moslem and also a Pura Mangkunegaran ruler. This article aims to describe the religio-cultural context of the funeral ceremony of KGPAA Mangkunegara IX. Using a qualitative method the study was provided with interviews and an audio-visual documentary to collect the data. The study found that during the funeral ceremony, there were many religious and cultural rites included, such as bathing, praying, and burying the late, wearing a Mataram royal palace as the funeral cloth, brobosan, the Javanese funeral song chanting, and tahlil. Some of them were done simultaneously while the other was not. This finding shows that the relationship between religion and culture is still being maintained in Javanese families with some adaptation due to the pandemic.